PENGARUH KEPEMIMPINAN TRANSAKSIONAL-TRANSFORMASIONAL PADA MODAL SOSIAL ANGGOTA ORGANISASI (Kasus untuk Karyawan Setingkat Staf pada Sebuah Perusahaan Otomotif di Jawa Tengah) - Prajogo, Wisnu (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2003)
Recently, social capital becomes a popular term in business world. Researchers believe that social capital has significant influence on employee performance. However, there has not been found any research examining how social capital can be built. This article tries to fill the gap by examining the effect of leader behavior to employees’ social capital. The results find strong support for the effect of transactional and transformational leadership to relational dimension ofsocial capital, and also strong support for the effect of transformational leadership to cognitive dimension of social capital. The results do not find any support for the effect of transactional and transformational leadership to structural dimension of social capital and the effect of transactional leadership to cognitive dimension of social capital.Keywords: transactional leadership, transformational leadership, social capital